Regional integration in the Asia Pacific issues and prospects. (OECD ; Bob Hawke Prime Ministerial Centre at the University of South Australia, 2005)
This report, published by the OECD's International Futures Program in cooperation with the Bob Hawke Prime Ministerial Center in Australia, aims to stimulate informed debate about the main integration issues facing the Asia-Pacific region in the decades ahead. It examines such issues as how the region compares to other regions of the world in terms of economic and political integration, regional cooperation on trade, investment and environment; and security and transportation concerns. The book concludes with Mike Moore's 'Reflections on Asia Pacific Integration'.--Publisher's description.